You can teach old dogs new clicks - the importance of teacher use of online content in a blended higher education course in Singapore (Journal of Applied Learning and Teaching, 2020)
Lecturers and teachers teaching in blended learning courses have myriad teaching strategies to employ and various online and face-to-face content at their disposal. There is still much we can find out about what and when to blend online and face-to-face components. In this study, we investigated the effects of the lecturer’s synchronous use of online content in the physical class on the subsequent asynchronous online participation and performance of higher education students. We found that the teacher’s use of the online content in the physical class has a positive effect on students’ subsequent online participation out-of-class. The results illustrate that intentional and integrated online and face-to-face components have positive impacts on students’ engagement and online participation. The results have implications for teachers, course designers, learners, and researchers of higher education blended courses.